VTA-NAc glutaminergic projection involves in the regulation of pain and pain-related anxiety - Abdul, Mannan; Yan, Hao-Qi; Zhao, Wei-Nan; Lyu, Xiao-Bin; Xu, Zheng; Yu, Xiao-Lu; Gao, Yi-Hong; Cao, Jun-Li (Frontiers in Molecular Neuroscience, 2022)
Background: Dopaminergic neurons in the ventral tegmental area (VTA) and their projections to many brain regions, especially the Nucleus accumbens (NAc), are well-known to establish chronic pain and emotional stress behaviors. However, the effects of VTA glutamatergic neurons on pain behaviors remain unclear. In the present study, we aimed to examine the role of VTA glutamatergic projections to NAc in pain and its related behavioral changes. Methods: Unilateral chronic sciatic nerve injury (CCI) or CFA intraplantar injections were performed in VGluT2-Cre and wild-type mice to establish the pain model. The Hargreaves test and Von Frey test were used for determining thermal and mechanical pain thresholds. The c-Fos labeling and electrophysiological recording were performed to verify CCI-induced firing rate changes in VTA glutamatergic neurons. The virus expression was confirmed by immunohistology staining and validated by the electrophysiological protocols. Then VTA-NAc glutamatergic projection was optogenetically and chemogenetically manipulated to investigate its roles in pain and related behavior changes. Open field tests, elevated maze tests, and sucrose preference tests were performed to test anxiety and depression behaviors Results: Glutamatergic neurons in VTA had efferent inputs to the NAc shell, and the chronic constrictive injury triggered a significant increase in firing rate and neuronal activity. Following this, the photoinhibition VTA-NAc glutamatergic pathway relieved CCI-induced neuropathic pain and CFA-induced acute and chronic inflammatory pain. Pathological neuropathic pain induced anxiety, and less sucrose preference, which was also relieved by inhibiting the VTA-NAc glutamatergic pathway. CONCLUSIONS: Taken together, glutamatergic inputs from the VTA to NAc contribute to chronic neuropathic and inflammatory pain, and also pain-related anxiety and depression behaviors, providing a mechanism for developing novel therapeutic methods in the future.